2022
DOI: 10.1002/cncr.34329
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated mononuclear cell telomere attrition in breast cancer survivors with depression history: A 2‐year longitudinal cohort study

Abstract: BACKGROUND: Cancer treatments are thought to accelerate biological aging, although this trajectory is highly variable. Depression is more prevalent in breast cancer survivors and is thought to be a vulnerability factor for biological aging. A lifetime history of depression and cumulative lifetime number of depression episodes could hypothetically be associated with an accelerated rate of biological aging as indexed by attrition of telomere length in a prospective cohort of breast cancer survivors who were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…The research conducted by Lansdorp showed that the differences in TL of individual white blood cell types increase with advancing age (depending on the number of cell divisions) compared to hematopoietic stem cells [ 110 ]. To achieve more reliable results, some authors prefer measuring telomere lengths in a specific type of white blood cells, e.g., mononuclear cells [ 111 ], granulocytes [ 112 ], or lymphocytes [ 113 , 114 ]. A meta-analysis by Adam et al summarized the results of 61 studies (a total of over 11.6 thousand cases with solid tumors and over 3 thousand cases with hematological malignancies) analyzing LTL, as well as TL changes in tumors and their surrounding tissue.…”
Section: Applications Of Telomeric Dna In Cancer Assessmentmentioning
confidence: 99%
“…The research conducted by Lansdorp showed that the differences in TL of individual white blood cell types increase with advancing age (depending on the number of cell divisions) compared to hematopoietic stem cells [ 110 ]. To achieve more reliable results, some authors prefer measuring telomere lengths in a specific type of white blood cells, e.g., mononuclear cells [ 111 ], granulocytes [ 112 ], or lymphocytes [ 113 , 114 ]. A meta-analysis by Adam et al summarized the results of 61 studies (a total of over 11.6 thousand cases with solid tumors and over 3 thousand cases with hematological malignancies) analyzing LTL, as well as TL changes in tumors and their surrounding tissue.…”
Section: Applications Of Telomeric Dna In Cancer Assessmentmentioning
confidence: 99%